2014
DOI: 10.9790/0853-13105106109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytological Grading in Breast Cancer Prognosis and its Histo-pathological Correlation

Abstract: Haematoxyline & Eosin, Papanicolau, and May-Grünwald-Giemsa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Singh et al showed that a better concordance between these grading systems can be achieved by examining 8 cell clusters. [14] Multiple regression analysis of various cytological features was used to assess the significance of each cytological parameter in the past. The coefficient of regression for all the parameters used in Robinson's grading were statistically significant (p=0.000) and all of them equally contributed in determining the cytological grading of the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al showed that a better concordance between these grading systems can be achieved by examining 8 cell clusters. [14] Multiple regression analysis of various cytological features was used to assess the significance of each cytological parameter in the past. The coefficient of regression for all the parameters used in Robinson's grading were statistically significant (p=0.000) and all of them equally contributed in determining the cytological grading of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson's grading system included the following criteria: Cell dissociation (clusters/single cells),Cell size (1-2/3-4/>5xRBC size), Cell uniformity (monomorphic/ mildly pleomorphic/ pleomorphic), nucleoli(indistitinct/ noticeable/prominent), nuclear chromatin (vesicular/ granular/clumped or cleaved) and nuclear margins (smooth/folds/buds or tufts).Each of the above criteria was given scores 1-3 and total sum of scores of all criteria were used to grade the tumours. Based on this, carcinoma breast cases were graded into grade I (score 6-11), grade II (score [12][13][14] and grade III (score 15-18) respectively. [1] Surgical specimens received for histopathological examination were fixed in 10% formalin.…”
Section: Methodsmentioning
confidence: 99%